Marginal grafts increase early mortality in liver transplantation - Bacchella, Telesforo; Galvão, Flávio Henrique Ferreira; Almeida, José Luiz Jesus de; Figueira, Estela Regina; Moraes, Andreza de; Machado, Marcel Cerqueira César (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Expanded donor criteria (marginal) grafts are an important solution for organ shortage. Nevertheless, they raise an ethical dilemma because they may increase the risk of transplant failure. This study compares the outcomes from marginal and non-marginal graft transplantation in 103 cases of liver transplantation due to chronic hepatic failure. DESIGN AND SETTING: One hundred and three consecutive liver transplantations to treat chronic liver disease performed in the Liver Transplantation Service of Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo between January 2001 and March 2006 were retrospectively analyzed. METHODS: We estimated graft quality according to a validated scoring system. We assessed the pre-transplantation liver disease category using the Model for End-Stage Liver Disease (MELD), as low MELD (< 20) or high MELD (≥ 20). The parameters for marginal and non-marginal graft comparison were the one-week, one-month and one-year recipient survival rates, serum liver enzyme peak, post-transplantation hospital stay and incidence of surgical complications and retransplantation. The signifi cance level was 0.05. RESULTS: There were no differences between the groups regarding post-transplantation hospital stay, serum liver enzyme levels and surgical complications. In contrast, marginal grafts decreased overall recipient survival one month after transplantation. Furthermore, lowMELD recipients of non-marginal grafts showed better one-week and one-month survival than did high-MELD recipients of marginal livers. After the fi rst month, patient survival was comparable in all groups up to one year. CONCLUSION: The use of marginal graft increases early mortality in liver transplantation, particularly among high-MELD recipients.